Efforts to Raise Local Residents Awareness of Environmental Cleanliness in Dokan Tourism Village, Karo Regency - Sinulingga, Jekmen; Tampubolon, Flansius (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Environmental cleanliness in tourist villages, especially in Dokan Village, is the main factor that needs to be considered to increase tourist visits. A clean environment will make visitors feel comfortable, besides that it will also create a healthy and clean environment. A tourist village is a village or area that has an unusual natural wealth, the village has natural resources that other villages may not have. The tourist village area is one of the places where environmental pollution most often occurs, which is carried out by the surrounding community and the outside community. The lack of public attention to the environment is very familiar, especially in today's era. Most of them think individually and only think about themselves. So we can see for ourselves how the impact of such a people's lifestyle on the environment in the tourist village of Dokan. Garbage that is disposed of improperly causes environmental pollution which will have a negative impact on the community itself. Therefore, environmental cleanliness also needs to be considered, not just talking about environmental cleanliness and how to overcome environmental pollution problems. So, if we can keep the environment clean and preserve the natural resources that are around us, it will certainly create a comfortable, clean, and beautiful living environment. In this case, it will be discussed about the role of the Dokan village community in implementing environmental cleanliness in the tourist village area. Environmental cleanliness in the tourist village area needs to be discussed because the area is a gathering place for people from inside and outside the village. This approach is intended so that the community has an attitude of caring about environmental cleanliness and preserving the natural resources in the surrounding villages.